A Rock Record of Complex Aeolian Bedforms in a Hesperian Desert Landscape: The Stimson Formation as Exposed in the Murray Buttes, Gale Crater, Mars. Issue 4 (21st April 2021) - Banham, Steven G.; Gupta, Sanjeev; Rubin, David M.; Edgett, Kenneth S.; Barnes, Robert; Van Beek, Jason; Watkins, Jessica A.; Edgar, Lauren A.; Fedo, Christopher M.; Williams, Rebecca M.; Stack, Kathryn M.; Grotzinger, John P.; et al.
Abstract: Lithified aeolian strata encode information about ancient planetary surface processes and the climate during deposition. Decoding these strata provides insight regarding past sediment transport processes, bedform kinematics, depositional landscape, and the prevailing climate. Deciphering these signatures requires a detailed analysis of sedimentary architecture to reconstruct dune morphology, motion, and the conditions that enabled their formation. Here, we show that a distinct sandstone unit exposed in the foothills of Mount Sharp, Gale crater, Mars, records the preserved expression of compound aeolian bedforms that accumulated in a large dune field. Analysis of Mastcam images of the Stimson formation shows that it consists of cross‐stratified sandstone beds separated by a hierarchy of erosive bounding surfaces formed during dune migration. The presence of two orders of surfaces with distinct geometrical relations reveals that the Stimson‐era landscape consisted of large dunes (draas) with smaller, superimposed dunes migrating across their lee slopes. Analysis of cross‐lamination and subset bounding surface geometries indicate a complex wind regime that transported sediment toward the north, constructing oblique dunes. This dune field was a direct product of the regional climate and the surface processes active in Gale crater during the fraction of the Hesperian Period recorded by the Stimson formation. The environment was arid, supporting a large aeolian dune field; this setting contrasts with earlier humid depositional episodes, recorded by the lacustrine sediments of the Murray formation (also Hesperian). Such fine‐scale reconstruction of landscapes on the ancient surface of Mars is important to understanding the planet's past climate and habitability. Plain Language Summary: Sedimentary rocks formed from sediments transported and deposited by the wind provide valuable information about the ancient environment, such as climate, wind direction, and the types of desert landforms that were present. This study focuses on the windblown sediments, now sandstone, imaged using the Mastcam instrument onboard the Mars Science Laboratory rover, Curiosity, at the Murray buttes inside Gale crater, between the 1383rd and 1455th Martian days (sols) of the mission. Analysis of the sedimentary structures in images shows that the Stimson formation at the Murray buttes was deposited by the wind in the form of compound sand dunes. These were large dunes with smaller dunes migrating across their surfaces. Analysis of the sedimentary structures generated by the complex interaction of these two scales of dune indicates that the large dunes migrated north, and that the smaller superimposed dunes migrated across the faces of the large dunes toward the northeast. The presence of large, wind‐driven dunes indicates that the region was extremely arid, and that—at the time the Stimson dune field existed—the interior of Gale crater was devoid of surface water, unlike the setting recorded by the older, underlying lake sediments of the Murray formation. Key Points: Compound cross‐bedding at the Murray buttes record the migration of oblique aeolian dunes. Large dunes (draas) migrated to the NNW, while superimposed dunes migrated NE. The bulk sediment transport direction was broadly toward the north The Stimson formation observed at the Murray buttes shares a common depositional architecture seen in other Stimson formation outcrop observed elsewhere on the traverse